IMPACTOS SOCIAIS DO MESTRADO EM GEOGRAFIA DA UNIVERSIDADE FEDERAL DE MATO GROSSO DO SUL – CAMPUS DE AQUIDAUANA: AS DISSERTAÇÕES DEFENDIDAS E A PERCEPÇÃO DOS EGRESSOS COMO FONTES DE ANÁLISE - Raiza Dias Amaral (2023)
Education in Brazil has been the target of claims for a long time, while the post-graduation is much more recent, being consolidated from the 1960s, with the creation of post-graduation courses in São Paulo and Rio de Janeiro. The Municipality of Aquidauana was the first in the state of Mato Grosso do Sul to offer a stricto sensu post-graduation course in geography, in 2000. However, due to the demands of the Coordination for the Improvement of Higher Level Personnel (CAPES) the course had to be transformed into a multicampi course, with the partnership of the Dourados (2002 to 2004) and Três Lagoas (2007 to 2009) campuses, ending its last class in 2009. With the restructuring of the campus and the hiring of new professionals, in 2014, a new course was started, currently in progress, which continues to contribute to the training of professionals. In this context, the research aimed to analyze the dynamics of implementation and operation of Master's courses in Geography at the campus of Aquidauana/MS, in the period from 2000 to 2022, in order to verify the impacts of PPGGEO/UFMS/CPAQ in the professional and technical training of human resources in the period from 2000 to 2022. For this, forms were sent via e-mail, Facebook and Instagram to the egresses of both courses. With this, 179 egresses of the two courses were identified, being115 in the first course and 64 in the second course, who finished their dissertations by 2022. The survey had the participation of 84 egresses. A form was also sent, via email, to the coordinators of the two courses, with questions about the dynamics and difficulties encountered in the courses, as well as their perceptions during their management. Sixty-three dissertations from the first course and 64 dissertations from the second course were analyzed, identifying the keywords and geographic analysis categories. The answers from the forms and the analyses of the dissertations were processed in the following software: IRaMuteq to process the qualitative answers, Excel for the quantitative answers, and Q-Gis for the creation of maps. As for the results, the importance of the course for the region, for the state and for Brazil was identified, since there are graduates distributed in several Brazilian regions, contributing to the professional qualification, job and career plan. It is concluded that the stricto sensu post-graduation in geography master's degree of UFMS/CPAQ provided relevant socioeconomic impacts on the professional lives of its graduates, in addition to the contribution to the geographic science in the state of Mato Grosso do Sul and in Brazil.